Testing the efficacy of alcohol labels with standard drink information and national drinking guidelines on consumers' ability to estimate alcohol consumption - Hobin, E.; Vallance, K.; Zuo, F.; Stockwell, Tim; Rosella, L.; Simniceanu, A.; White, C.; Hammond, D. (Oxford University Press, 2018)
Medical Council on Alcohol and Oxford University Press. All rights reserved. Aims: Despite the introduction of national drinking guidelines in Canada, there is limited public knowledge of them and low understanding of 'standard drinks (SDs)' which limits the likelihood of guidelines affecting drinking behaviour. This study tests the efficacy of alcohol labels with SD information and Canada's Low-Risk Drinking Guidelines (LRDGs) as compared to %ABV labels on consumers' ability to estimate alcohol intake. It also examines the label size and format that best supports adults' ability to make informed drinking choices. Methods: This research consisted of a between-groups experiment (n = 2016) in which participants each viewed one of six labels. Using an online survey, participants viewed an alcohol label and were asked to estimate: (a) the amount in a SD; (b) the number of SDs in an alcohol container and (c) the number of SDs to consume to reach the recommended daily limit in Canada's LRDG. Results: Results indicated that labels with SD and LRDG information facilitated more accurate estimates of alcohol consumption and awareness of safer drinking limits across different beverage types (12.6% to 58.9% increase in accuracy), and labels were strongly supported among the majority (66.2%) of participants. Conclusion: Labels with SD and LRDG information constitute a more efficacious means of supporting accurate estimates of alcohol consumption than %ABV labels, and provide evidence to inform potential changes to alcohol labelling regulations. Further research testing labels in realworld settings is needed. Short summary: Results indicate that the introduction of enhanced alcohol labels combining standard drink information and national drinking guidelines may be an effective way to improve drinkers' ability to accurately assess alcohol consumption and monitor intake relative to guidelines. Overall support for enhanced labels suggests probable acceptability of introduction at a population level.